Mechanical behavior analysis and bearing capacity calculation of CFG pile composite foundation on coral sand site - Li, Xiaobin; Zhang, Ruiyuan; Yang, Zhao; Chen, Peishuai; Ji, Fuquan; Wen, Bing (Frontiers in Earth Science, 2023)
Coral sand foundation formed by hydraulic fill often faces the problem of poor bearing capacity. This paper proposed for the first time to apply CFG pile composite foundation to coral sand sites to verify the feasibility of this scheme and understand its mechanical characteristics. Firstly, taking on-site coral sand as the research object, a pile sand interface shear test was conducted to clarify the mechanism of pile side friction. At the same time, the ultimate bearing capacity of CFG pile and its composite foundation was measured through in-situ static load tests. Then, based on the strength parameters of the pile sand interface revealed by indoor tests, numerical simulations were conducted to analyze the bearing characteristics of CFG piles and their composite foundations. Finally, a method for calculating the vertical bearing capacity of rigid piles in composite foundation considering interface parameters was proposed. The results showed that the bearing capacity characteristic values of single pile and composite foundation meet the design requirements; The interface friction angle and cohesion together increased the ultimate side friction by 64.41%; The load is mainly borne by the pile tip resistance, and the increase of the interface friction angle will make the proportion of the side friction load first increase and then decrease more obviously; The pile soil stress ratio first increased and then tended to stabilize as the interface strength increased. Compared with the field static load test results, the rationality of the calculation method for composite foundation rigid piles was verified. This study may have reference significance for the design and construction of coral sand foundation treatment in offshore island and reef projects.